Between the empire and the nation state: the problem of the Russian-Norwegian frontier and Sami occupation in the 19th – early 20th centuries. Issue 1 (2nd January 2019) - Zaikov, Konstantin
ABSTRACT: The article, based on a complex of sources, from the archives of Russia, Norway and the United States, presents the results of a study of little-known pages of the history of Russian–Norwegian relations in the Far North of the 19th – early 20th centuries. The basic idea is to trace a change in policy towards traditional indigenous peoples of the Russian-Norwegian frontier under the influence of the emerging nation state (Norway) and the Russian Empire. The study of this issue is limited to the Arctic region of the Russian–Norwegian border zone in 1826−1905 and is connected with the exacerbation of diplomatic relations under the influence of a seemingly insignificant question concerning Sami occupations. The archaic fishing culture of the Russian Sami (East Sami), which did not recognise hermetically sealed political borders, became the subject of a struggle between the young national state − Norway and the multinational empire − Russia that experienced a new intellectual renewal, a gradual transition from traditionalism to nationalism at the close of the nineteenth century. A minor issue of the fishing rights of several dozen East Sami in the territory of northern Norway became the personification of the 'Russian threat' image for the Norwegian Finnmark. This tendency manifested itself in the attempts of Norwegian officials to ethnocultural consolidation of the frontier through active church construction and in an effort to revise the provisions of the additional Protocol of 1834. On the other hand, the visible growth of the Norwegian presence in western Murman and the facts of East Sami oppression in Norway became the symbols of the 'Norwegian threat', territorial expansion, which by the Arkhangelsk community's opinion began in 1826 with the territorial concessions to Norway during the delimitation of the interstate borders. At the turn of the twentieth century, the Russian authorities tried to protect the East Sami occupations by revising the Protocol of 1834.